Pemenuhan Kebutuhan dan Komunikasi Organisasi dalam Menangani Konflik di Budiman Swalayan - Fairana, Aura; Ramadani, Intan; Saputra, Relly Anjar Vinata Wisnu (Program Studi Ilmu Komunikasi Universitas Negeri Padang, 2024)
In every organization or company there is always conflict. Conflict is something that is natural and permanent, always there. The purpose of this research is to analyze how Budiman supermarket handles conflicts that occur. This research uses a descriptive qualitative approach with data collection methods of observation, interviews and documentation. This research uses the theory of basic human needs that can trigger conflict. The results of this study discuss how conflicts are viewed, the kinds of conflicts, the causes of conflicts, the process of conflicts, and conflict resolution strategies at Budiman Supermarket. As well as explaining that there are various human needs that can trigger conflict in Budiman supermarket. And organizational communication plays an important role in resolving conflicts that occur.